2019
DOI: 10.1007/s00436-019-06273-2
|View full text |Cite
|
Sign up to set email alerts
|

Antarctophthirus microchir infestation in synanthropic South American sea lion (Otaria flavescens) males diagnosed by a novel non-invasive method

Abstract: Antarctophthirus microchir is a sucking louse species belonging to the family Echinophthiriidae and has been reported to parasitize all species of the subfamily Otariinae, the sea lions. Former studies on this ectoparasite mainly required fixation, immobilization, or death of host species and especially examinations of adult male sea lions are still very rare. Between March and May 2018, adult individuals of a unique “urban” bachelor group of South American sea lions ( Otaria flavescens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In the last years, development and application of non-invasive sampling techniques in the field of parasitology of marine mammals have impressively expanded the possibilities of examining the endo-and ectoparasite fauna of free-ranging animals in vivo, while clearly leaving the animals unmolested in their natural habitats (Kleinertz et al, 2014;Hermosilla et al, 2015;Hermosilla et al, 2016aHermosilla et al, ,b, 2018ade Vos et al, 2018;Ebmer et al, 2019;Vélez et al, 2019). Thereby, the present study exhibits advantages and usefulness of applied non-invasive scat collection methods, showing their applicability in the field of marine mammal parasitology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, development and application of non-invasive sampling techniques in the field of parasitology of marine mammals have impressively expanded the possibilities of examining the endo-and ectoparasite fauna of free-ranging animals in vivo, while clearly leaving the animals unmolested in their natural habitats (Kleinertz et al, 2014;Hermosilla et al, 2015;Hermosilla et al, 2016aHermosilla et al, ,b, 2018ade Vos et al, 2018;Ebmer et al, 2019;Vélez et al, 2019). Thereby, the present study exhibits advantages and usefulness of applied non-invasive scat collection methods, showing their applicability in the field of marine mammal parasitology.…”
Section: Discussionmentioning
confidence: 99%
“…They also display altered feeding habits. Interspecific interactions occur on a daily basis and are decisive for maintenance of diverse endo-and ectoparasite life cycles in this urban colony (Sepúlveda et al, 2015;Hermosilla et al, 2016a;Cornejo-Galaz, 2017;Ebmer et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…xation techniques with low handling times implying conservation aspects [12,59]. Ebmer et al [60] showed the successful application of a non-invasive sampling method by using a lice comb screwed on a telescopic rod for taking lice samples within a unique 'urban' colony of South American sea lions (O. avescens) in Valdivia, Chile. This technique could de nitively be applied during sampling of other synanthropic seals.…”
Section: Discussionmentioning
confidence: 99%
“…Skin samples of marine mammals can be used for trace element detection (Al, V, Cr, Mn, Cu, Zn, As, Se, Rb, Sr, Mo, Cd, Pb), but only if a full biopsy is collected, which, depending on size, can actually be an invasive procedure [188]. Truly minimally invasive samples of dead superficial skin cells collected with combs can be used for ectoparasite detection, for example, Antarctophthirus microchir in American sea lions (Otaria flavescens) [189]. Skin scrapings are commonly used on several species for Sarcoptes scabiei detection.…”
Section: Hair Feathers and Skinmentioning
confidence: 99%